Added value of frailty and social support in predicting risk of 30-day unplanned re-admission or death for patients with heart failure: An analysis from OPERA-HF. (1st March 2019) - Sokoreli, I.; Cleland, J.G.; Pauws, S.C.; Steyerberg, E.W.; de Vries, J.J.G.; Riistama, J.M.; Dobbs, K.; Bulemfu, J.; Clark, A.L.
Abstract: Background: Models for predicting the outcome of patients hospitalized for heart failure (HF) rarely take a holistic view. We assessed the ability of measures of frailty and social support in addition to demographic, clinical, imaging and laboratory variables to predict short-term outcome for patients discharged after a hospitalization for HF. Methods: OPERA-HF is a prospective observational cohort, enrolling patients hospitalized for HF in a single center in Hull, UK. Variables were combined in a logistic regression model after multiple imputation of missing data to predict the composite outcome of death or readmission at 30 days. Comparisons were made to a model using clinical variables alone. The discriminative performance of each model was internally validated with bootstrap re-sampling. Results: 1094 patients were included (mean age 77 [interquartile range 68–83] years; 40% women; 56% with moderate to severe left ventricular systolic dysfunction) of whom 213 (19%) had an unplanned re-admission and 60 (5%) died within 30 days. For the composite outcome, a model containing clinical variables alone had an area under the receiver-operating characteristic curve (AUC) of 0.68 [95% CI 0.64–0.72]. Adding marital status, support from family and measures of physical frailty increased the AUC (p < 0.05) to 0.70 [95% CI 0.66–0.74]. Conclusions: Measures of physical frailty and social support improve prediction of 30-day outcome after an admission for HF but predicting near-term events remains imperfect. Further external validation and improvement of the model is required. Highlights: 1 in 5 patients hospitalized for heart failure will have an unplanned re-admission within 30 days of discharge. Assessing diverse aspects of frailty improves prediction of near-term outcomes. A patient receiving support from their family may be less likely to be admitted to hospital. Physical and social frailty improve the discrimination between patients who did or did not experience the primary outcome. Next to physical and social frailty, emotional or mental frailty should not be overlooked either.